Ibuprofen blood plasma levels and onset of analgesia. (19th November 2012) - Mehlisch, D. R.; Sykes, J.
Summary: Background:  Ibuprofen is widely available as an over‐the‐counter treatment for pain and fever. New formulations are now available, with varying pharmacokinetic profiles. However, few studies have been specifically designed to examine the relationship between ibuprofen plasma levels and onset of analgesia. This study aimed to determine a value, or range of values, for the blood plasma level of ibuprofen at which onset of analgesia could be expected. Methods:  Placebo‐controlled clinical trials, investigating the efficacy and pharmacokinetics of ibuprofen 200 mg and 400 mg, were identified. A retrospective posthoc analysis was performed on data from trials that incorporated time to perceived pain relief as an endpoint and the incidence of confirmed/unconfirmed perceptible pain relief was assessed. Mean ibuprofen blood plasma levels were computed at various time points using data from pharmacokinetic trials. Results:  Two trials were identified with sufficient data to analyse time to onset of analgesia (Current Controlled Trials ISRCTN73768226, ISRCTN86009231). For 400 mg ibuprofen, the incidence of confirmed perceptible pain relief was significantly greater vs. placebo at 20 min post dosing (both studies). For 200 mg ibuprofen, significance was reached at 20 min (one study). In the 17 trials, with data on plasma concentrations for patients receiving 400 mg ibuprofen, the weighted mean value at 20 min post dosing was 8.4 μg/ml (95% confidence interval, 6.8–10.1). Conclusions:  Results of this study provide useful information for the development of new ibuprofen formulations. Further prospective studies and studies using other endpoints to define efficacy and onset would be of interest.